A Community-Based Cross-Sectional Study on Human Papillomavirus (HPV) Vaccination: Knowledge Gaps and Attitudinal Determinants among Women of Reproductive Age in Al-Jafara, Libya - Ahlam Althabet; Anwar Elmahgubi; Noran Erayani (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: Human Papillomavirus (HPV) is a primary causative agent of cervical cancer, a considerable health concern for women globally. Comprehending knowledge, awareness, and attitudes towards HPV and its vaccination among women of childbearing age is critical for effective prevention approaches. Objective: This study evaluated knowledge, awareness, and attitudes regarding HPV infection and vaccination among women aged 18-35 in Aljafara. Methods: A cross-sectional study was conducted with 140 women using a structured questionnaire to gather data on demographics, knowledge about HPV, and vaccination attitudes. Descriptive statistics and correlation analyses were carried out on the data. Results: Most participants (68.8%) were aged 26-30, married (62.8%), and held a bachelor’s degree (50%). While 75% recognized the higher risk of HPV in females, 56.5% were unaware that HPV causes nearly all cervical cancers. Additionally, 81.4% supported male HPV vaccination to protect partners. Healthcare workers had significantly higher knowledge scores (p < 0.001). No significant correlations were found between knowledge scores and age, marital status, or education level. Conclusion: Significant knowledge gaps exist among Libyan women of childbearing age regarding HPV, even among healthcare professionals. While attitudes towards vaccination are generally positive, uncertainties about effectiveness and eligibility remain. To enhance Libyans’ awareness of HPV and vaccination, comprehensive educational efforts are required.